"Growth Chart Study in Children Under 5 Years Old in Rural Area of Khoramabad Province" - F Majlesi; B Nikpoor; B Golestan; F Sadre (Tehran University of Medical Sciences, 2001)
Growth chart is the best measure for weight monitoring of children. Most factors that affect child heath show their effect on child weight. This cross sectional and descriptive analytical study was achieved to estimate malnutrition prevalence and effective factors in children under 5 years old in rural area of Khoramabad province. 555 girls and 570 boys were chosen from health houses by cluster sampling. Data were gathered through questionnaires. verbal interviews and child weighing. Nutritional status was estimated via weight/age index and the data were analysed by chi-square test. The results show 7.7% malnutrition among the children in this area. Factors that influence the nutritional status were: Frequency of diarrhea and acute respiratory infection, birth weight, duration of breast feeding and milk formula.